Multifunctional Arabinoxylan-functionalized-Graphene Oxide Based Composite Hydrogel for Skin Tissue Engineering - Khan, Muhammad Umar Aslam; Razak, Saiful Izwan Abd; Hassan, Anwarul; Qureshi, Saima; Stojanović, Goran M.; Ihsan-Ul-Haq, (Frontiers in Bioengineering and Biotechnology, 2022)
Wound healing is an important physiological process involving a series of cellular and molecular developments. A multifunctional hydrogel that prevents infection and promotes wound healing has great significance for wound healing application in biomedical engineering. We have functionalized arabinoxylan and GO by the hydrothermal method, through crosslinking GO-arabinoxylan and PVA with TEOS to get multifunctional composite hydrogels. These composite hydrogels were characterized by FTIR, SEM, water contact angle, and mechanical testing to determine structural, morphological, wetting, and mechanical behavior, respectively. The swelling and biodegradation were also conducted in different media. The enhanced antibacterial activities were observed against different bacterial strains (E. coli, S. aureus, and P. aeruginosa), anticancer, and biocompatibility assays were found effective against U-87 and MC3T3-E2 cell lines due to the synergic effect of hydrogels. In vivo activities were conducted using a mouse full-thickness skin model and an accelerated wound healing was found without any major inflammation within 7-days with improved vascularization. From the results, these composite hydrogels might be potential wound dressing materials for biomedical application.